HUBUNGAN UMUR, PARITAS, ANEMIA DAN KEHAMILAN GANDA DENGAN KEJADIAN BBLR DI RSUD PURI HUSADA TEMBILAHAN TAHUN 2015-2017 - Dewi Erlina Asrita Sari; Yulia Hasmita (STIKES HUSADA GEMILANG, 2019)
Birth weight is the weight of the baby weighed within 1 hour after birth. In Riau, the infant mortality rate is still relatively high – 28 per 1000 live births – by the most common causes of neonatal death are respiratory problems, low birth weight and sepsis. This study aims to identify the correlation among ages, parity, anemia, gemelli and LBW at RSUD Puri Husada Tembilahan in 2015–2017. This research is analytical descriptive with case control. The population of the research were all babies with LBW at RSUD Puri Husada Tembilahan in 2015–2017 with sample of case group and control group. The sampling technique used in this research was systematic random sampling. The data collected was secondary data by using checklist sheets, so they were analyzed through the univariate and bivariate analysis. The results show that there is a correlation between the age of the mother and LBW (p value = 0,000 with OR 7,114), there is a relationship between parity and LBW (p value = 0,000 with OR 7,731), there is a correlation between anemia and LBW (p value = 0,000 with OR 121,207), and there is a relationship between gemilli and LBW (p value = 0,000 with OR 2,975). Accordingly, this research is supposed to reduce the LBW rates and would recommend on providing cares on pregnant women with LBW risk.